The Influence of Flexible Working Arrangement on Job Performance with Supervisor Support and Work-Family Conflict as Mediators - Sekarini, Ni Kadek Ayuni; Rachmawati, Riani (Universitas KH. Abdul Chalim Mojokerto, 2026)
The Greater Jakarta area (Jabodetabek) is known for its severe traffic congestion, which significantly impacts employees’ daily lives. Flexible Working Arrangement (FWA) has emerged as a potential solution to reduce commuting burdens and improve work efficiency. In addition to offering flexibility for employees, FWA benefits organizations by lowering operational costs such as office space and equipment. Globally, the adoption of FWA has increased, including in Indonesia, driven by digital transformation and post-pandemic work pattern shifts. However, the effectiveness of FWA on Job performance (JP) remains under scrutiny, as JP is a critical factor in achieving organizational goals. While FWA may help reduce Work-Family Conflict (WFC), some studies suggest it may also increase WFC due to blurred boundaries and dual roles. Supervisor support is therefore essential to ensure that FWA policies are implemented effectively and support employee performance. This study aims to examine the influence of FWA on JP, considering the mediating roles of WFC and Supervisor support, particularly in the Jabodetabek area. Data were collected from 244 employees who are eligible for FWA and live with their families. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that FWA has a positive and significant effect on JP, helping employees reduce stress and fatigue, thus working more effectively. Supervisor support partially mediates this relationship, while WFC does not. Managerial implications highlight the importance of consistent support from supervisors to foster a productive and harmonious work environment.